Influence of natural clouds on the performance of solar cell systems in Iraq - Hiba Nadhim Ameen Al-Kaoaz; Omar Sharaf Al-deen Yehya Al-Yozbaky (Institute of Advanced Engineering and Science, 2023)
Solar energy generated by photovoltaic (PV) technology can be supplied to standalone systems, as it combines efficiency and cost-effectiveness. However, this combination is achieved only after considering the effects of shading, which can significantly influence electrical output. The primary factor that influences the use of solar energy in electricity generation is irradiation. PV cells are significantly impacted by shading, where the output of the PV cell reduces in the presence of a shadow. In this study, the researchers have presented an experimental analysis of how shading affects two PV cells, using the series and parallel configurations. The experimental work is installed at the University of Mosul, Department of Electrical Engineering, Renewable Lab (Iraq). MATLAB was used to simulate, evaluate, and compared the results to understand the effects of shading on PV cell output. This research offers an analytical technique to determine the probable effects of Partial shadowing conditions on PV power generation. The results provide the effects of partial shadowing in an annual performance loss of ≥10–30%. The orientation of the PV panels' tilt angle has an impact on their output power. When the tilt angle deviates from its ideal value, the PV panel's output drops off substantially.